2019
DOI: 10.4317/jced.55124
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dental fluorosis in three zones of Ecuador

Abstract: Background: To determine the prevalence of dental fluorosis in 10-12 year-old school children, in three provinces of the inter-andean Region of Ecuador: Imbabura, Pichincha and Chimborazo, as well as the relationship between certain factors, considering that the latest studies go back to the year 2009. Material and Methods: A cross-sectional and observational study was proposed. A sample of 599 was calculated at 95% of confidence considering population projections for children between 10 and 12 old of three zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
3
13
1
8
Order By: Relevance
“…In the present study, the incidence of DF showed no significant differences between males and females. This result was consistent with the previous findings of Molina-Frechero et al [ 2 ] and Zhou et al [ 6 ] However, Armas-Vega et al [ 27 ] reported that females were more likely to have DF. Regretfully, they did not analyze the reasons for this interesting result.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the incidence of DF showed no significant differences between males and females. This result was consistent with the previous findings of Molina-Frechero et al [ 2 ] and Zhou et al [ 6 ] However, Armas-Vega et al [ 27 ] reported that females were more likely to have DF. Regretfully, they did not analyze the reasons for this interesting result.…”
Section: Discussionsupporting
confidence: 93%
“…Armas-Vega et al demonstrated that the prevalence of dental fluorosis was of 89.96% in 2019. [ 27 ] Verma and his colleagues found that the incidence of DF was 68.8% in 2011. [ 9 ] Molina-Frechero et al [ 2 , 19 ] reported that Mexico also increased average dental fluorosis from 26% in 2002 to 59% in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies present differences in the prevalence of DF according to sex 29 , while still others report no significant association between DF and age, sex, or socioeconomic status 12 . Considering economic situation, the population of the present study is vulnerable, with only 25.32% of the families receiving a minimum wage and with 3-7 individuals in 81.58% of the families.…”
Section: Discussionmentioning
confidence: 91%
“…However, with the economic factor in this population treated as a constant, the bivariate analysis showed a correlation with minimum-wage family income ($247 USD), although the severity was explained by other variables (p = 0.09) in the adjusted analysis. Other studies report correlations between socioeconomic status and DF, observing a relationship between higher income and being able to afford to buy toothpaste and other topical fluorides 16,28,29,32 . Among the statistically significant factors in the present study (p <0.05), the amount of toothpaste (pea-sized volume) used was associated with severity, though the use of more than a pea-sized volume did not present an association, but since its OR=12.52 was high, it was probably not significant because very few children used it (n=13).…”
Section: Discussionmentioning
confidence: 98%
“…Epidemiological information on DDEs is substantial within and between populations, as it can contribute to the assessment and monitoring of environmental or systemic factors and to the detection of possible etiological factors responsible for their occurrence [ 23 ]. In Ecuador, there are no studies of DDEs, but there are data on dental fluorosis in different regions of the country, specifically in the north of Ecuador, where the levels of dental fluorosis are high [ 24 , 25 ]. Since dental enamel is a biological marker of the expression of different types of lesions, we believe it is essential to develop the first epidemiological report of DDEs in the country to determine the prevalence of enamel alterations in schoolchildren aged 6 to 12 years in urban and rural environments of three provinces of Ecuador that make up the southern region of the country.…”
Section: Introductionmentioning
confidence: 99%